Упростить Если можно, то с объяснением [latex] t^{1/4} + (1- t^{1/2} ) / (1 + t^{1/4} )[/latex]

Упростить Если можно, то с объяснением [latex] t^{1/4} + (1- t^{1/2} ) / (1 + t^{1/4} )[/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]t^\frac{1}{4}+\frac{1-t^\frac{1}{2}}{1+t^\frac{1}{4}}=t^\frac{1}{4}+\frac{(1)^2-(t^\frac{1}{4})^2}{1+t^\frac{1}{4}}=t^\frac{1}{4}+\frac{(1-t^\frac{1}{4})(1+t^\frac{1}{4})}{1+t^\frac{1}{4}}=t^\frac{1}{4}+1-t^\frac{1}{4}=1[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы